The Impact of Coffee and Caffeinated Beverage Consumption on Dental Caries: A Review - Harniati Ramli; Ramadhan Tosepu; Hilda Harun; La ode Muhammad Sety; Mubarak; Syawal Kamiluddin Saptaputra (Journal of Health Science and Pharmacy, 2026)
Background: Dental caries is one of the most common oral health problems worldwide and remains a challenge for global public health. This disease occurs due to an imbalance between the processes of demineralization and remineralization of enamel, influenced by biological factors, behavior, and patterns of food and beverage consumption. Coffee and caffeinated beverages are part of the modern lifestyle widely consumed, yet they have a dual effect on dental health. On one hand, bioactive compounds such as polyphenols, chlorogenic acid, and caffeine have the potential to provide antibacterial effects against Streptococcus mutans, but on the other hand, the content of acids and added sugars can lower salivary pH and increase the risk of caries. Objective: This study aims to systematically review the latest scientific evidence regarding the effects of coffee and caffeinated beverage consumption on the risk of dental caries, from microbiological, biochemical, and clinical perspectives. Research method: The study used a Systematic Literature Review (SLR) approach with PRISMA guidelines. Articles were obtained from electronic databases such as Google Scholar, ResearchGate, PubMed, Scopus, and ScienceDirect using keywords coffee, caffeine, dental caries, saliva pH, polyphenols, as well as the effects of coffee and caffeinated beverage consumption on dental caries. Results: Review results indicate that excessive coffee consumption or coffee with added sugar can lower saliva pH below the critical threshold (5.5), potentially triggering enamel demineralization and promoting the growth of Streptococcus mutans. The tannin and chromogen content in coffee also causes staining and increases the roughness of the tooth surface, facilitating plaque adhesion. However, some studies report protective effects from sugar-free coffee due to bioactive compounds such as polyphenols and chlorogenic acid, which have antibacterial and antioxidant activities. The results also indicate that the type of coffee, preparation method, and consumption frequency are determining factors in both the cariogenic and anticariogenic effects of coffee. Conclusion: Coffee consumption has a bidirectional effect on dental health. Coffee with added sugar and consumed in excess can increase the risk of cavities, whereas sugar-free coffee consumed in moderation has the potential to provide a protective effect on enamel through antibacterial and antioxidant activities. Therefore, education about healthy coffee consumption habits and maintaining oral hygiene are important steps to minimize the risk of cavities and maximize the benefits of bioactive compounds in coffee on dental health. Keywords: Coffee, Caffeine, Dental Caries, Salivary pH, Polyphenols